Analisis Spasial Perkembangan Sektor PertanianDi Kabupaten Ngawi Tahun 2004 - 2013 - Nofitasari, Yesi; , Drs. H.M Musiyam MTP; , Dra. Umrotun,M.Si (2016)
The agricultural sector is a category of superior sector that potentially to develop the region economic sector. The agricultural sector is main sector for Ngawi. From the five sub-sectors of agriculture (crops, plantations, livestock, forestry, and fisheries), sub-sector of crops is the contributor largest for the total value of agricultural production, especially rice commodity. This study conducted to know the progress of agricultural sector, sub-sector of agriculture, and the spatial distribution of agriculture sub-sector which have the advantage and contributed greatly for the economic growth in Ngawi during 2004 until 2013. The method used in this research is quantitative research methods, that is processing the numeral data by using spatial approach which used to know the spatial distribution of potential the agricultural sector in Ngawi. The analyzing data used LQ (Location Quotient), analysis unit per agriculture sector and mapping the spatial distribution of analysis unit per district. The results of this study are Ngawi have superior agriculture sector such as sub-sector of crops, livestock, and forestry. The potential sub-sector of crops based on the potential land are at sub-districts of Sine, Kendal, Paron, Kedunggalar, Widodaren, and Karanganyar. The potential sub-sector of livestock are at sub-districts Sine, Kendal, Widodaren, Paron, Geneng, and Ngawi. The potential sub-sector of forestry is the second largest teak wood manufacture after Banyuwangi at East Java. The superiority of three sub-sectors are related with the physical and non-physical factors, and the factors that involved the agricultural sector in the district of Ngawi.